A Parallel Design Study to Assess the Bioequivalence of Generic and Branded Hydroxychloroquine Sulfate Tablets in Healthy Volunteers - Liu, Y.-M.; Chen, Q.; Zhang, M.-Q.; Liu, G.-Y.; Jia, J.-Y.; Pu, H.-H.; Liu, Y.; Hu, C.-Y.; Lu, C.; Wang, W.; Cao, W.-E.; Song, B.; Song, Y.-X.; Zhu, J.-M.; Yu, C. (Arzneimittelforschung, 2012)
Hydroxychloroquine (HCQ) is a racemic 4-aminoquinoline derivative that was first introduced as an antimalarial, and subsequently applied to the treatment of autoimmune diseases such as rheumatoid arthritis and systemic lupus erythematosus. Information on the pharmacokinetics of HCQ in healthy volunteers, especially in a Chinese population is limited, and this study was conducted to provide support for a generic product to obtain marketing authorization in China.The aim of the present study was to compare the pharmacokinetics and assess bioequivalence of a new generic test and the branded reference hydroxychloroquine sulfate tablets in healthy volunteers.This was a parallel, open-label, randomized, single-dose, 1-period fasting study. 54 healthy subjects were randomly assigned (1:1) to receive 200 mg hydroxychloroquine sulfate tablets of the test or the reference formulation. 15 blood samples were collected and whole blood concentrations of HCQ were determined by a validated liquid chromatography-isotopic dilution mass spectrometry method. Log-transformed Cmax and AUC0–24 values were used to test for bioequivalence. The 2 formulations were considered bioequivalent if 90% confidence intervals (CIs) for the log-transformed ratios of Cmax and AUC0–24 were within the predetermined bioequivalence range of 80–125%. Tolerability was evaluated throughout the study by vital signs, physical examinations, clinical laboratory tests, 12-lead electrocardiograms, and interviews with the subjects about adverse events.54 healthy subjects were enrolled and completed the study (mean [SD] age, height, body weight, and BMI were 23.9 [2.4] years, 168.9 [5.0] cm, 61.3 [5.4] kg, and 21.5 [1.7] kg/m2), 27 subjects per group. No formulation or sequence effects were observed. The mean values of Cmax and AUC0–24 for the test and reference formulations of HCQ (197.6 and 199.0 ng/mL, 2460.1 and 2468.3 ng/mL/h) were not significantly different. The 90% CIs of the ratios of Cmax and AUC0–24 were 99.3% (98.1–102.1%), 99.7% (98.9–101.4%), respectively. 4 subjects (7.41%) experienced a total of 4 mild AEs (headache and microscopic hematuria, 1 each; and increase in plasma triglycerides, 2).The results of this study suggest that the test and reference hydroxychloroquine sulfate tablets are bioequivalent. Both formulations were generally well tolerated.
Keywords: Hydroxychloroquine; bioequivalence; pharmacokinetics; parallel; LC–IDMS